Harmonic Analysis of Three Phase AC Voltage Regulators Using Thyristor - Diode Switches - N.H. Malik (Journal of King Saud University: Engineering Sciences)
Based upon numerical evaluation of Fourier coefficients, complete harmonic analysis is carried out for various three phase, AC thyrode voltage regulators. Various quantities of interest are computed and presented in the form of normalized curves for balanced R-L loads of different power factors. It is shown that the line controlled circuits offer the best overall performance and are superior in performance than the conventionally used thyristor voltage controllers.